DOMINASI MEDIA SOSIAL DALAM ARUS INFORMASI: KAJIAN TERHADAP AKSI BELA ISLAM - Ninuk Riswandari (Ilmu Psikologi Universitas Yudharta Pasuruan)
“Aksi Bela Islam” that occurred during the period of October 2016 until February 2017 has attracted the attention of many parties. The case of blasphemy against religion by the Governor of DKI Jakarta Basuki Tjahaya Purnama became the forerunner of these actions. All started from video uploading speech Governorof DKI Jakarta in facebook account owned by Buni Yani. Videos that have been edited prior to uploading have angered Muslims. It can not be denied that the presence of social media has changed the way of exchanging information in the community. The spread of information occurs so quickly and extensively without knowing the distance and time. Interpretation of information also varies among individuals. The edited video snippet by removing one word makes the meaning of the sentence as a whole to change. Message overload continues to take care of the same case through the mass media and the opinion leader also reinforces the initial belief in the meaning of the message.